Development, Preparation, and Biomedical Applications of DNA-Based Hydrogels - Jian, Xueting; Feng, Xiaoyi; Luo, Yuning; Li, Fangjie; Tan, Junyan; Yin, Yuli; Liu, Yang (Frontiers in Bioengineering and Biotechnology, 2021)
Hydrogels have outstanding research and application prospects in the biomedical field. Among them, the design and preparation of biomedical hydrogels with DNA as building blocks has attracted increasing research interest. DNA-based hydrogel not only has the skeleton function of hydrogel, but also retains its biological functions, including its excellent selection specificity, structural designability, precise molecular recognition ability, outstanding biocompatibility, and so on. It has shown important application prospects in the biomedical field, such as drug delivery, biosensing, and tissue engineering. In recent years, researchers have made full use of the characteristics of DNA molecules and constructed various pure DNA-based hydrogels with excellent properties through various crosslinking methods. Moreover, via introducing functional molecules or elements, or combining with other functional materials, a variety of multi-functional DNA-based hybrid hydrogels have also been constructed, which expand the breadth and depth of their applications. Here, we described the recent development trend in the area of DNA-based hydrogels and highlighted various preparation methods of DNA-based hydrogels. Representative biomedical applications are also exempliﬁed to show the high performance of DNA-based hydrogels. Meanwhile, the existing problems and prospects are also summarized. This review provided references for the further development of DNA-based hydrogels.